2020
DOI: 10.1038/s41386-020-0700-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of trauma and PTSD on epigenetic prediction of lifespan and neural integrity

Abstract: Post-traumatic stress disorder (PTSD) is a debilitating disorder that develops in some people following trauma exposure. Trauma and PTSD have been associated with accelerated cellular aging. This study evaluated the effect of trauma and PTSD on accelerated GrimAge, an epigenetic predictor of lifespan, in traumatized civilians. This study included 218 individuals with current PTSD, 427 trauma-exposed controls without any history of PTSD and 209 subjects with lifetime PTSD history who are not categorized as curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
66
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 63 publications
18
66
0
2
Order By: Relevance
“…Third, homelessness might be the breaking point for those who have pre-existing behavioral health conditions or a prior history of trauma [ 22 ]. Homeless migrants’ families cumulate risk factors for developing PTSD that could impact physical [ 23 ] and other mental disorders (depression, anxiety disorders) [ 24 , 25 ] and also impact biological (cellular aging [ 26 ]) and social functioning [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Third, homelessness might be the breaking point for those who have pre-existing behavioral health conditions or a prior history of trauma [ 22 ]. Homeless migrants’ families cumulate risk factors for developing PTSD that could impact physical [ 23 ] and other mental disorders (depression, anxiety disorders) [ 24 , 25 ] and also impact biological (cellular aging [ 26 ]) and social functioning [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, one of the main symptoms of PTSD is an elevated rumination characterised by repetitive, negative self-focused cognition, and it has been reported that a reduced functional connectivity between the isthmus cingulate and the left precuneus within the DMN is linked to this high level of rumination [22]. Lifetime trauma burden and suffering from both current and lifetime PTSD have been reported to cause GrimAge acceleration [23]. It has also been found that patients with Alzheimer's disease (AD) and in the prodromal stage of AD have decreased DMN functions and precuneus GM volume compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Acting through oxidative stress and inflammation pathways, PTSD and traumatic experiences are thought to advance cellular aging and reduce life span. 273 These adverse experiences triggering psychological stress result in accelerated biological aging and alteration in DNA methylation patterns, which are recorded on a person's epigenetic clock. GrimAge, an epigenetic predictor of lifespan, combines methylation levels at specific CpG sites that predict biological age combined with additional biomarkers (sex, smoking pack-years, and others).…”
Section: Stress and Epigeneticsmentioning
confidence: 99%
“…Chronic inflammation as found in PTSD appears to be involved in the relationship between PTSD and GrimAge acceleration. 273 Low-grade inflammation, as measured by serum C-reactive protein, and immunosenescence contribute to aging. This low-grade inflammation, referred to as inflammaging, is an imbalance between pro-and antiinflammatory pathways and is common in the elderly.…”
Section: Stress and Epigeneticsmentioning
confidence: 99%